ANALISIS GETARAN TANAH (GROUND VIBRATION) HASIL PELEDAKAN OVERBURDEN DI SITE TAMBANG AIR LAYA SELATAN PT. BUKIT ASAM (PERSERO), TBK TANJUNG ENIM SUMATERA SELATAN - Can Royen Situmorang; Raimon Kopa; Sumarya Sumarya (Departemen Teknik Pertambangan FT UNP, 2015)
Ground vibration effect directly caused by blasting activities. This effect can be negative value if hedamaged against the influence of the wall bech or building structures. To generate a safe blasting necessary measurements of ground vibration against vibration resulting from blasting so that each can be known maximum number of explosives are best used for a certain distance. By analysis the peak particle velocity and scale distance then it can be determined the value of the peak particle velocity that’s safe and appropriate for the conditions of the surrounding rocks. Blasting activities carried out at PIT south mine air laya PT. Bukit Asam (Persero) Tbk with a pattern of blasting hole by hole, using a surface delay detonator 109 ms, 42 ms and in hole delay detonator 500 ms. Blasting is not done with one explosion, but rather is done gradually or made into some Initiation Point (IP) blasting alternately after done checking. The system uses non-electric and triggers the initial explosion in the form of electric detonators connected to the blasting machine using lead wire. The results of the measurement of the soil vibration obtained PPV average actual 1,72 mm/s, PPV the average regression analysis (prediction) 1,64 mm/s. For geting value PPV 2 mm/s at a distance of 500 m maximum field required as much 57,594 kg of ANFO. The use of blasting method with long period dalay, blasting made into some IP and Line Drilling is already effective and economical to reduce vibration Standard PT. BA PPV 2 mm/s and the SNI 7571 PPV 3 mm/s.